Brain MRS correlates with mitochondrial dysfunction biomarkers in MELAS‐associated mtDNA mutations. Issue 6 (5th May 2021) - Gramegna, Laura L.; Evangelisti, Stefania; Di Vito, Lidia; La Morgia, Chiara; Maresca, Alessandra; Caporali, Leonardo; Amore, Giulia; Talozzi, Lia; Bianchini, Claudio; Testa, Claudia; Manners, David N.; Cortesi, Irene; et al.
Abstract: Objective: The purpose of this study was to investigate correlations between brain proton magnetic resonance spectroscopy ( 1 H‐MRS) findings with serum biomarkers and heteroplasmy of mitochondrial DNA (mtDNA) mutations. This study enrolled patients carrying mtDNA mutations associated with Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke‐like episodes (MELAS), and MELAS‐Spectrum Syndrome (MSS). Methods: Consecutive patients carrying mtDNA mutations associated with MELAS and MSS were recruited and their serum concentrations of lactate, alanine, and heteroplasmic mtDNA mutant load were evaluated. The brain protocol included single‐voxel 1 H‐MRS (1.5T) in the medial parieto‐occipital cortex (MPOC), left cerebellar hemisphere, parieto‐occipital white matter (POWM), and lateral ventricles. Relative metabolite concentrations of N‐acetyl‐aspartate (NAA), choline (Cho), and myo‐inositol (mI) were estimated relative to creatine (Cr), using LCModel 6.3. Results: Six patients with MELAS (age 28 ± 13 years, 3 [50%] female) and 17 with MSS (age 45 ± 11 years, 7 [41%] female) and 39 sex‐ and age‐matched healthy controls (HC) were enrolled. These patients demonstrated a lower NAA/Cr ratio in MPOC compared to HC ( p = 0.006), which inversely correlated with serum lactate ( p = 0.021, rho = −0.68) and muscle mtDNA heteroplasmy ( p < 0.001, rho = −0.80). Similarly, in the cerebellum patients had lower NAA/Cr ( p < 0.001), Cho/Cr ( p = 0.002), and NAA/mI ( p = 0.001) ratios, which negatively correlated with mtDNA blood heteroplasmy ( p = 0.001, rho = −0.81) and with alanine ( p = 0.050, rho = −0.67). Ventricular lactate was present in 78.3% (18/23) of patients, correlating with serum lactate ( p = 0.024, rho = 0.58). Conclusion: Correlations were found between the peripheral and biochemical markers of mitochondrial dysfunction and brain in vivo markers of neurodegeneration, supporting the use of both biomarkers as signatures of MELAS and MSS disease, to evaluate the efficacy of potential treatments.